Wife of the life of the party - Chaplin, Lita Grey 1908-1995; Vance, Jeffrey 1970- (Filmmakers, 1998)
When she was fifteen, Chaplin signed her as the leading lady in The Gold Rush and changed her name to Lita Grey. She was forced to leave the production when, at the age of sixteen, she became pregnant with Chaplin's child. She married Chaplin in Empalme, Mexico, in November 1924